FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KEPUTUSAN PEMBELIAN PRODUK HOUSE OF HARUMI DI SURAKARTA - Y. Djoko Suseno, Fransisca Harumi Pardamean (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2015)
This study aims to analyze the influence that occurred between (1) the quality poduk on purchasing decisions, (2) the price of the purchase decision, (3) the distribution channel to the purchasing decision, (4) the promotion of the purchase decision, (5) the attractiveness posting messages to purchasing decisions, (6) trust on purchase decisions, (7) the reputation of the purchase decision, (8) the quality of service to the buying decision, and (9) buying interest on product purchasing decisions House of Harumi in Surakarta. Population House of Harumi 2015 as many as 150 people. Samples were taken based on the table Cohen and Morrison were 108 people with accidental sampling technique. Test Data instrument validity and reliability test. Data were analyzed using classical assumption (multicollinearity, autocorrelation and normality test) and test hypotheses (multiple linear regression, t-test, the accuracy of the model (F) and test the coefficient of determination (R2)). The data obtained are measured with Likert scale. The results of the analysis of data obtained all the data obtained from the questionnaire is valid and reliable, no data multicollinearity, heteroscedasticity does not happen, no autocorrelation and each normally distributed variables 0.771. For variables that significantly influence the purchasing decisions of products House of Harumi only occurs in the variable quality of the product price, promotion, quality of service, and buying interest. As for the variable distribution channels, the attractiveness of the posts, reputation and trust does not significantly influence the purchasing decisions of products House of Harumi. The variables that influence most dominant in this research is the quality of the product. Keywords: purchasing decisions, product quality, price, distribution channels, promotion, attractiveness of the posts, reputation, trust, quality of service, buying interest